2021
DOI: 10.1183/13993003.00284-2021
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analyses reveal new stage-specific features of COVID-19

Abstract: The current pandemic of coronavirus disease 19 (COVID-19) has affected more than 160 million of individuals and caused millions of deaths worldwide at least in part due to the unclarified pathophysiology of this disease. Therefore, identifying the underlying molecular mechanisms of COVID-19 is critical to overcome this pandemic. Metabolites mirror the disease progression of an individual by acquiring extensive insights into the pathophysiological significance during disease progression. We provide a comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 43 publications
6
60
0
Order By: Relevance
“…Many viruses are reported to enhance glycolysis, which allows the rapid production of energy and other substrates necessary for viral replication [ 3 ]. Consistent with such mode, metabolomic, proteomic and transcriptomic analyses have revealed increased levels of pyruvate, pyruvate kinase and lactate dehydrogenase (LDH) in COVID-19, all of which are metabolites or enzymes of glycolysis, indicating enhanced glucose metabolism for lactate fermentation [ 52 , 53 , 54 , 55 ]. Glycolysis is of vital importance for SARS-CoV-2 to replicate [ 56 , 57 ].…”
Section: Metabolism Reprogramming In Covid-19 Infectionmentioning
confidence: 98%
“…Many viruses are reported to enhance glycolysis, which allows the rapid production of energy and other substrates necessary for viral replication [ 3 ]. Consistent with such mode, metabolomic, proteomic and transcriptomic analyses have revealed increased levels of pyruvate, pyruvate kinase and lactate dehydrogenase (LDH) in COVID-19, all of which are metabolites or enzymes of glycolysis, indicating enhanced glucose metabolism for lactate fermentation [ 52 , 53 , 54 , 55 ]. Glycolysis is of vital importance for SARS-CoV-2 to replicate [ 56 , 57 ].…”
Section: Metabolism Reprogramming In Covid-19 Infectionmentioning
confidence: 98%
“…The human blood sera metabolome (defined as small molecules <1500–2000 Da) reflects the organism's metabolic state and is widely used to gain a deeper understanding of the pathogenesis of diseases. Recent reports of metabolomics studies highlight the pivotal role of cellular metabolites in programming immune response to SARS-CoV-2 infection, but nevertheless, none of the studies so far have addressed the metabolomic changes during the recovery of infection in a longitudinal manner ( 9 13 ). Considering the extremely high heterogeneity of the COVID-19 disease and lack of promising predictive biomarkers, we believe that implications of longitudinal metabolite profiling may be beneficial in understanding the underlying mechanisms of the diverse course of the disease and promote the early identification of people at increased risk of severe illness from COVID-19 and related complications.…”
Section: Observationmentioning
confidence: 99%
“…Tryptophan catabolism is linked to infection-induced inflammation in several infections including Chlamydia psittaci, herpes simplex virus (HSV)-2, Leishmania donovani, and Toxoplasma gondii [39,[41][42][43][44]. In fact, due to its significance in orchestrating the immune responses in event of an infection, changes in tryptophan metabolism have been studied in people infected with SARS-CoV-2 [11,20,36,37]. Metabolomic study conducted by Thomas et al concurred with our findings and showed tryptophan metabolism to be the leading pathway affected by SARS-CoV2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, various 'omic' techniques have been used by multiple groups, identifying potential targets/pathways affected by SARS-CoV2 infection [6][7][8][9]. Indeed, there have been several metabolomics studies conducted so far that identify the dysregulated pathways in COVID-19, but further work in this area is important to draw meaningful conclusions regarding the disease pathogenesis in COVID-19 [2,3,8,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%